The Importance of Iron in the Body's Metabolic Processes - Kudratova Z.E; Muxamadiyeva L.A.; Hamidova Z.A. (Global Scientific Publishing, 2023)
Iron helps to support many important body functions, affecting vitality, concentration, gastrointestinal processes, the immune system and the regulation of body temperature. A shortage or excess of it has an immediate effect on well-being.
Keywords: iron; gastrointestinal processes; erythropoiesis; haemoglobin